Testosterona, estradiol e doença arterial coronariana em homens adultos - Callou, Emmanuela Quental [UNIFESP] (2010)
Introduction: Cardiovascular diseases (CVDs) represent the main cause of death in Brazil, and among them especially the coronary artery diseases (CADs). Men present higher incidence and mortality rates for CAD than women. One of the explanations for this fact may be the possibly deleterious effect of testosterone on the male cardiovascular system and the protective effect of estradiol on the female cardiovascular system. However, recent studies in the literature indicate that testosterone has an either protective or neutral effect on the male cardiovascular system, while high levels of estradiol in men have been correlated to higher rates of morbidity and mortality from cardiovascular diseases. Objectives: To carry out a review of the literature regarding the relationship between testosterone and cardiovascular disease in men, to evaluate the existing relationships among total testosterone, bioavailable testosterone, free testosterone, free androgen index (FAI), sex hormone binding globulin, estradiol, free estrogen index (FEI), estradiol/testosterone ratio and FEI/FAI ratio and coronary artery disease in men; to understand the role of the sex hormone binding globulin as a new component of the metabolic syndrome. Material and Methods: The review of the literature regarding the relationship between testosterone and cardiovascular disease was performed using the PubMed database and the keywords testosterone and cardiovascular disease. The relationship between sex steroids and CAD was evaluated by a case-control study performed on men submitted to coronary angiography at the Instituto Dante Pazzanese de Cardiologia. The role of the sex hormone binding globulin (SHBG) as a new component of the metabolic syndrome was evaluated using the data obtained by the study “Estradiol but not Testosterone is Related to Coronary Artery Disease”. Results: The results were presented in three articles, namely: ARTICLE 1 - “Serum Testosterone and Cardiovascular Disease in Men”; ARTICLE 2 - “Estradiol but not Testosterone is Related to Coronary Artery Disease in Men”; ARTICLE 3 - (being prepared for submission) - “Sex hormone binding globulin, the novel component of metabolic syndrome?”. Conclusions: The studies retrieved from the literature which evaluated the relationship between testosterone and cardiovascular disease presented small numbers of participants and selected samples, which indicated the need for further studies to evaluate the role of testosterone in CVD in men. The findings presented suggest a positive correlation between estradiol and FEI levels with CAD. A neutral effect of total testosterone, bioavailable testosterone, free testosterone, free androgen index, SHBG, estradiol/testosterone ratio and FEI/FAI ratio on the incidence of this pathology was observed. Low levels of SHBG seem to correlate positively with the components of the metabolic syndrome, but further studies are necessary to evaluate this parameter as a new component of this syndrome.